2018
DOI: 10.1002/aenm.201801781
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cycling Stability of Macroporous Bulk Antimony‐Based Sodium‐Ion Battery Anodes Enabled through Active/Inactive Composites

Abstract: Engineering strategies based on “nanostructuring” and “active/inactive composites” are commonly used separately to improve the performance of alkali‐ion battery electrodes. Here, these two strategies are merged to further enhance the performance of alloy‐type alkali‐ion battery anodes. Specifically, macroporous antimony (Sb)/magnesium fluoride (MgF2) active/inactive composite material is used as a high‐performance Na‐ion battery anode. The porous Sb phase with pore size in the sub‐micrometer range acts as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 76 publications
0
32
0
Order By: Relevance
“…In literature, alloy‐type metals have often been used in the nanoparticle form in order to ensure high utilization in sodiation reactions, but recent publications have shown that also bulk antimony and bismuth could be stable during cycling. [ 260,261 ] In ref. [ 260 ] , the mixture of macroporous antimony and an inactive magnesium fluoride (Figure 25d) sustained over 300 cycles.…”
Section: Alloy‐type Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…In literature, alloy‐type metals have often been used in the nanoparticle form in order to ensure high utilization in sodiation reactions, but recent publications have shown that also bulk antimony and bismuth could be stable during cycling. [ 260,261 ] In ref. [ 260 ] , the mixture of macroporous antimony and an inactive magnesium fluoride (Figure 25d) sustained over 300 cycles.…”
Section: Alloy‐type Materialsmentioning
confidence: 99%
“…[ 260,261 ] In ref. [ 260 ] , the mixture of macroporous antimony and an inactive magnesium fluoride (Figure 25d) sustained over 300 cycles. Bulk bismuth has turned into porous material after several cycles of operation in a glyme‐based electrolyte (Figure 25e), allowing to use it as the anode material without further processing.…”
Section: Alloy‐type Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the past few years, tremendous efforts have been devoted to improving the cyclic stability by modifying alloying materials through carbon coating, porous architectures, and nanostructural designs. [ 8–11 ] The nanostructure of the bismuth anode was capable of achieving less or even zero strain for SEI formation, as well as providing a fast electron/ion transfer pathway for enhanced rate capabilities. For example, the Bi@graphene nanocomposite and bismuth nanodots confined in the metal–organic framework derived carbon arrays exhibited dramatic improvement, in terms of their specific capacity.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38] Secondly, SbNs exhibit outstanding electron conductivity of $1.6 Â 10 4 S m À1 for fast electron transfer. [39][40][41] Thirdly, the diffusion energy barrier for Li atom within SbNs is only $0.48 eV, which benets the transfer of Li + within SbNs material. 42 Lastly a stable chemical bonding can be formed between Sb atom and S atom, which will facilitate the adsorption of LiPSs to Sb material.…”
Section: Introductionmentioning
confidence: 99%